Urban-rural differences in the successful aging among older adults in China - Keying Song; Jiedan Luo; Xiaodong Cao; Zijian Zhao (PLoS ONE, 2025)
This study aimed to reveal urban-rural disparities in successful aging among Chinese older adults and the impact of gender and age on aging outcomes. We utilized the Successful Aging Index (SAI), a multidimensional measure encompassing social, economic, bio-clinical, psychological, and lifestyle factors. Scores on the SAI range from 0 to 10, with higher scores signifying better aging. Data was sourced from the 2018 Chinese Longitudinal Healthy Longevity Survey, comprising 7,315 participants. Urban older adults (OU) had significantly higher SAI scores than rural older adults (OR), with averages of 4.32 ±  1.44 and 3.85 ±  1.24, respectively (p < 0.001). Men showed more successful aging than women, regardless of their residence (p < 0.001). OU had better financial and educational status and higher social activity scores, except for friend interaction (p < 0.001). They were more physically active (p < 0.001), more adherent to the Mediterranean diet (p < 0.001), and less likely to smoke (p = 0.018). However, OU had a higher prevalence of cardiovascular disease risk factors compared to OR (p < 0.001). Notably, depression scores were similar between OU and OR (p = 0.129). In summary, significant urban-rural differences in successful aging are evident among Chinese older adults, with urban-dwelling older adults aging more successfully than their rural peers. Men, irrespective of their place of residence, experience more successful aging outcomes than women.